Semiotic System of Clothes and Decorations in Cao Xueqin’s Novel “Red Tower Dream” - L. Zhang; L. Zheng (Научный диалог, 2020)
The article discusses the features of the presentation of the clothing and jewelry system in one of the works of Cao Xueqing, “Red Tower Dream”, recognized by the top of Chinese literature. It is noted that the analysis of this novel is addressed in different aspects by researchers both in China and in Russia. This article is devoted to the study of clothing and jewelry as a symbolic system in the novel. 173 different words and phrases that are used to designate clothes and jewelry were identified in 44 chapters of the first 80. Using several fragments of the description of the clothes and jewelry of the heroes as an example, their social and some personality characteristics were analyzed. Conclusions are drawn about the peculiarities of the presentation of the costume of a man and a woman in a novel reflecting the realities of ancient China. It is shown that the details of clothing and jewelry of the heroes of the novel testify to their estate, wealth and occupation. It is noted that the original descriptions of the costume and jewelry in the novel may differ from the translated version, so the Chinese reader, based on linguistic and extralinguistic knowledge about the culture of clothing in ancient China, can provide a more accurate and complete picture of the social characteristics of the characters than the Russian-speaking reader.